Wound Healing: A Comprehensive Review - Almadani, Yasser H.; Vorstenbosch, Joshua; Davison, Peter G.; Murphy, Amanda M. (Seminars in Plastic Surgery, 2021)
Wound healing is an intricate, tightly regulated process that is critical to maintaining the barrier function of skin along with preserving all other skin functions. This process can be influenced by a variety of modifiable and nonmodifiable factors. As wound healing takes place in all parts of the human body, this review focuses on cutaneous wound healing and highlights the classical wound healing phases. Alterations in any of these phases can promote chronic wound development and may impede wound healing.
Keywords: wound healing; inflammation; chronic wounds